(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
At present, knowledge of a foreign language is of great importance for any person, since intercultural relations have taken an important place in almost all spheres of human activity. Therefore, many schools provide intensive training in this subject. At the same time, there are a number of problems that are difficult to solve with a very small number of hours.